Techno-Economic Assessment of a Rotatable Fish Grill for Charcoal and Briquette - Amponsah, Shadrack Kwadwo; Asare, Helena (Discoveries in Agriculture and Food Sciences, 2023)
Charcoal and briquette fuel material were each assessed for use in a locally manufactured rotatable fish grill. Fresh African Catfish (Clarias gariepinus) samples averagely weighing 500±54g were taken from a fishpond managed under a recirculating aquaculture system (RAS) at the study location. Three repetitions of a Completely Randomized Design (CRD) were used, and LSD was calculated at p ≤ 0.05. The findings indicate that compared to briquette fuel material, charcoal used much more energy. Similarly, grilling using charcoal required much more time (53 minutes) than grilling with briquettes (37 minutes). The energy efficiency of the grill did not differ significantly between charcoal (93.6%) and briquette (92.9%). Similarly, no significant difference in specific fuel consumption was observed for charcoal (1.06) and briquette (0.90) fuel material. Fish grilled over charcoal or briquette produced cooking yields of 72% and 70%, respectively. Breakeven for charcoal and briquette assuming the grill is under a custom hiring arrangement was estimated at 1010.9 hours and 991.83 hours, respectively. Future studies should examine organoleptic evaluation of fish grilled on rotatable grills to determine whether the finished product is acceptable to consumers. Nile Tilapia (Oreochromis niloticus) could be the subject of a similar investigation.